2021
DOI: 10.1162/jocn_a_01748
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Attention and Spatial Attention Distinctly Influence Long-term Memory Encoding

Abstract: Our attention is critically important for what we remember. Prior measures of the relationship between attention and memory, however, have largely treated “attention” as a monolith. Here, across three experiments, we provide evidence for two dissociable aspects of attention that influence encoding into long-term memory. Using spatial cues together with a sensitive continuous report procedure, we find that long-term memory response error is affected by both trial-by-trial fluctuations of sustained attention and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…This suggests that the benefit of focusing selective attention in VWM generally occurs independently from the level of sustained attention. Converging with our results, recent research observed similar independent contributions of sustained and selective attention on long-term memory (LTM) performance for continuous features (deBettencourt et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This suggests that the benefit of focusing selective attention in VWM generally occurs independently from the level of sustained attention. Converging with our results, recent research observed similar independent contributions of sustained and selective attention on long-term memory (LTM) performance for continuous features (deBettencourt et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Healthy younger adults can maintain, on average, four visual representations accessible in VWM. This estimate, however, is subject to variation between individuals (Cowan, 2010;Luck & Vogel, 2013) and also within-individuals, reflecting trial-by-trial fluctuations due to changes in sustained attention (Adam et al, 2015;Adam & Vogel, 2017;deBettencourt et al, 2019deBettencourt et al, , 2020Fukuda et al, 2015;Mrazek et al, 2012;Rademaker et al, 2012). The contribution of attentional fluctuations to VWM performance has been examined, for example, by asking participants to rate their attentional levels towards the task (Adam & Vogel, 2017;Unsworth & Robison, 2016) or by interspersing memory probes in a sustained attention task at moments associated with high and low levels of sustained attention (deBettencourt et al, 2018(deBettencourt et al, , 2019.…”
Section: Tracking Attentional States: Assessing the Relationship Betw...mentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the present work is first to simultaneously examine potential memory enhancements of informative, uninformative, and no prestimulus cues on multiple memory measures (i.e., corrected hit rates, familiarity, recollection, and source memory). Our findings expand on prior studies examining the influence of prestimulus cues on memory with at most two types of cues, such as informative vs. no prestimulus cues (Lin et al, 2015) and informative vs. uninformative prestimulus cues (deBettencourt et al, 2021;Kafkas, 2021;Kafkas & Montaldi, 2018). For example, Lin and colleagues (2015) had participants encode scenes that were preceded by either an informative prestimulus cue that signaled the valence of the upcoming scene (i.e., X = negative, O = neutral) or no prestimulus cue.…”
Section: Discussionsupporting
confidence: 75%
“…Linking memory brain states to attention is critical given the impact that both memory and attention states have on behavior. Lapses in sustained attention negatively impact subsequent memory [29][30][31] and engagement in a retrieval state can come at the expense of engaging an encoding state, leading to diminished subsequent memory 9 . To the extent that the retrieval state extends beyond controlled, episodic memory retrieval, there are potentially wide-ranging consequences throughout cognition for engaging in this brain state.…”
Section: Introductionmentioning
confidence: 99%